2019
DOI: 10.4314/njt.v38i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Stability and durability of sawdust ash-lime stabilised black cotton soil

Abstract: The assessment of the durability of twelve cylindrical samples of black cotton soil, a well-known problem soil, stabilized with a combination of 4%lime and 16% sawdust ash were carried out in laboratory using the methods of [1] and that recommended by [2] and [3]. The results showed that the unconfined compressive strength of the samples under varying curing and soaking conditions ranged from 1217kPa to 265kPa while the durability indices were 59.51% and 59% respectively. Thus, the stabilizers have elevated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…70 sieve [119,122] applied in lateritic soil, an increase in the OMC and a decrease in the MDD and plasticity index were observed with the addition of the SDA mixture, additionally, the UCS values were increased to a peak SDA value at a percentage of 6%; finest sawdust ash passing No. 200 sieve [115,118,121,123] applied to lateritic soil and black cotton soil have evidenced that the addition of sawdust ash caused a decrease in the plasticity index (PI) and MDD, while OMC and CBR increased for maximum values obtained with a 4% addition of sawdust ash; additionally complementary materials have been combined with sawdust ash to improve soil properties, like eggshell ash [116], lime [117] natural fibers of sisal [66] and Kernel palm shell ash [125], observing considerable improvement of mechanical properties of soils, increasing MDD and decreasing OMC in the case of eggshell ash, while lime increase the durability index and natural fibers decreased the MDD while the OMC and UCS increased. Other region with abundant research on the use of sawdust ash is India, where studies carried out varying percentages of sawdust ash addition, ranging from 2% and up to 25%, showed that CBR and OMC increased while MDD decreased for a clay soil from Rajouri region [93] and the expansive soil from Sitarganj region [126], but the increase of percentage addition of sawdust ash applied to Black cotton soil from Kadapa region increase the MDD value and the permeability coefficient decrease [128]; other research shows that, the addition of sawdust and coconut fiber on a kaolinitic clay from Kerala region shows that the OMC and strength of the clay increased, while a decrease in its MDD was observed; additionally, it was analyzed the effect of adding some percentages of the mixture of sawdust ash and Lime (SDAL) in an expansive black cotton soil [127], to improve compressive strength and swelling characteristics and increase its suitability use in construction, it was observed that MDD and UCS have a peak of 2% SDAL content and then decrease while the OMC decreases with an SDAL content of 1%, increases to a content of 2%, and then decreases with an increase in SDAL and CBR value increases up to 2% of SDAL and thereafter decreases; complementary research carried out adding sawdust ash and fly ash on a lateritic soil from Soraba Taluk region [129], showed that the expansion rate and plasticity index decreased and CBR increased with the percentage of addition, while the MDD increased for an addition of 10% and then decreased similar behavior to OMC that increased to an addition of 20% and then decreased.…”
Section: Sawdust Ashmentioning
confidence: 99%
“…70 sieve [119,122] applied in lateritic soil, an increase in the OMC and a decrease in the MDD and plasticity index were observed with the addition of the SDA mixture, additionally, the UCS values were increased to a peak SDA value at a percentage of 6%; finest sawdust ash passing No. 200 sieve [115,118,121,123] applied to lateritic soil and black cotton soil have evidenced that the addition of sawdust ash caused a decrease in the plasticity index (PI) and MDD, while OMC and CBR increased for maximum values obtained with a 4% addition of sawdust ash; additionally complementary materials have been combined with sawdust ash to improve soil properties, like eggshell ash [116], lime [117] natural fibers of sisal [66] and Kernel palm shell ash [125], observing considerable improvement of mechanical properties of soils, increasing MDD and decreasing OMC in the case of eggshell ash, while lime increase the durability index and natural fibers decreased the MDD while the OMC and UCS increased. Other region with abundant research on the use of sawdust ash is India, where studies carried out varying percentages of sawdust ash addition, ranging from 2% and up to 25%, showed that CBR and OMC increased while MDD decreased for a clay soil from Rajouri region [93] and the expansive soil from Sitarganj region [126], but the increase of percentage addition of sawdust ash applied to Black cotton soil from Kadapa region increase the MDD value and the permeability coefficient decrease [128]; other research shows that, the addition of sawdust and coconut fiber on a kaolinitic clay from Kerala region shows that the OMC and strength of the clay increased, while a decrease in its MDD was observed; additionally, it was analyzed the effect of adding some percentages of the mixture of sawdust ash and Lime (SDAL) in an expansive black cotton soil [127], to improve compressive strength and swelling characteristics and increase its suitability use in construction, it was observed that MDD and UCS have a peak of 2% SDAL content and then decrease while the OMC decreases with an SDAL content of 1%, increases to a content of 2%, and then decreases with an increase in SDAL and CBR value increases up to 2% of SDAL and thereafter decreases; complementary research carried out adding sawdust ash and fly ash on a lateritic soil from Soraba Taluk region [129], showed that the expansion rate and plasticity index decreased and CBR increased with the percentage of addition, while the MDD increased for an addition of 10% and then decreased similar behavior to OMC that increased to an addition of 20% and then decreased.…”
Section: Sawdust Ashmentioning
confidence: 99%
“…; 'd=O [7w6] "OwW|t C}rwR x@ hwQat |Qwr@ |=yOt=H Ovv=t |m =N |}=}rk =} |}=}rk C= Rri R= |r=DU} Qm |}=yC=m}r}Uwv}twr; '=yC}rwR w [AlO 4 ] 5 ? }mQD R= xm OvDUy s}Urm w s} Q=@ 's}Uv= QDU= 's}R}vt 's}U=DB 's}OU 1 |x]@= Q "OwW|t xOy=Wt 1 pmW QO C}rwR Q=DN=U "Ov};|t OwHw x@ [SiO 4 ] 4 R= "Ov=xOw@ R=UpmWt xQ=wty |Dtw=kt C=}YwYN p}rO x@ |}xv=O |=yl=N sOa w sm Ctw=kt 'CN=wvm} w CUU |}xU=t |=yl=N xOta |=y|oS}w u=t}U uOwRi= VwQ 'CUU |}xU=t l=N C}@FD CyH "CU=yu; |oOv@UJ QO xRwQt= [1] "CU= u=UOvyt |xO=iDU= OQwt OQ@Q=mQB |=yxv}Ro R= |m} u=wva x@ l=N KqY= hQY |r=t `@=vt R= |yHwD p@=k VN@ '|v= Qta |=yxSwQB R= |Q=}U@ p=L QO |QyW j]=vt QO |oOvR |= Q@ R}v |]}LtCU} R \}=QW u=tRty "OwW|t R= xO=iDU= xrtH R= |R=Uy@ |=yVwQ |NQ@ uOw@ |tU u}vJty "CU= Ct=Nw |]}LtCU} R CqmWt |NQ@ RwQ@ ?Hwt u=t}U w ly; Ovv=ty |}=}t}W O=wt [42] "OwW|t |v}tRQ} R ? ; |=yxQiU Q}Ut Q}}eD w =yl =N |oOwr; Q}_v V}B QO |oOwr; Vy=m |= Q@ = Q =y|Qw=vi u} QDuQOt u=t}U CavY xm |r=L QO QO |O=}R syU 'u=t}U pkv w ptL w O}rwD Ov}=Qi hrDNt pL=Qt =t= 'CU= xDiQo w u=t}U uD l} O}rwD |= Q@ OyO|t u=Wv C=ar=]t "OvQ=O CU} R\}Lt |oOwr; pY=L Ov=tUB w |@v=H pwYLt xm CU= xQ=l=N 'xOW xQ=W= O=R O=wt u}= R= |m} Ovv=t |}=yOQ@ Q=m xQ=l=N "CU= ?wJ uOQm xQ= Ovv=t ?wJ =@ Q=m C=}rta R= R= |Q@?wJ C=Hv=NQ=m QO "OQ=O ?wJ p=eR =} w ?wJ Q}tN CN=U QO xO=iDU= xm OwW|t xO=iDU= uOQm ?=}U; C=}rta |= Q@ CNwU u=wva x@ |O}rwD |=yxQ=l=N xQ=l=N QDUm =N R= "CU= xQ=l=N QDUm =N 'xQ=l=N uOv= RwU R= xOv=t}k=@ pwYLt [18w17] "OQm xO=iDU= l=N |R=Uy@ QO =} w uD@ CN=U QO u=wD|t C=}YwYN QO xQ=l=N Q}F -=D OQwt QO u= QoWywSB R= |Q=}U@ 'p}rO u}ty x@ "CU= xDW=O l=N X=wN QO |}=RU@ Q}F -=D Qt= u}= xm Ov=xOQm xar=]t l=N |UOvyt QO OYQO 9 w 6 '3 |vRw Q}O=kt =@ xQ=l=N Q}F=D |UQQ@ QO 2019 |Q}@O w u}OD V}=Ri= x@ QHvt xQ=l=N 3 uOwRi= xm OvDi=} QO |UQ |=yl=N |m}vmDwS Q=DiQ CUWv w ?…”
Section: "|Qwltld |Q=wimentioning
confidence: 99%
“…George and Braide (2014) studied the effect of SDA whose method of processing was not defined, on Nigerian deltaic laterites and demonstrated how it can improve some engineering properties. Obeta et al (2019) also obtained saw dust ash by closed incineration and used 16% of the SDA with 4% lime to black cotton soil in its stabilization, the results showed that SDA with lime as stabilizer can improve the otherwise non-durable soil into the marginal durable zone.…”
Section: Introductionmentioning
confidence: 99%